2015
DOI: 10.1155/2015/709191
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Retina Are Not Involved in the Genesis of Visual Hallucinations in Parkinson’s Disease

Abstract: Parkinson's disease (PD) is characterized by motor and nonmotor symptoms. Nonmotor symptoms include primarily visual hallucinations (VH). The aim of our study was to establish whether patients with PD and visual hallucinations (PDH+) have structural changes of retina detected by an optical coherence tomography (OCT) in comparison with PD patients without visual hallucinations (PDH−). We examined 52 PD patients (18 with VH, 34 without VH) and 15 age and sex matched healthy controls. Retinal nerve fiber layer (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However, some studies reported that there was no macular thinning in PD. Kopal et al did not show any significant difference in RNFL thickness and macular thickness between PD patients and healthy controls [12]. They concluded that functional and structural changes in the retina are not related to visual symptoms in PD.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, some studies reported that there was no macular thinning in PD. Kopal et al did not show any significant difference in RNFL thickness and macular thickness between PD patients and healthy controls [12]. They concluded that functional and structural changes in the retina are not related to visual symptoms in PD.…”
Section: Discussionmentioning
confidence: 91%
“…Some studies demonstrated a significant reduction in RNFL thickness among PD patients [8][9][10][11]. Some studies, however, reported that there is no difference in RNFL thickness between those two groups [7,12,13]. Controversial results may be predetermined by the subject selection, small sample sizes, or variable sensitivity of optical coherent tomography (OCT) instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for such a pathological compensatory process has been observed in Charles Bonnet syndrome (152). In Parkinson's disease, one study demonstrated a relationship between RNFL thinning and VH ( 153), but a second study found no evidence for such a link (154). A recent study in schizophrenia (155,156) indicated that four separate samples of patients with both auditory and visual hallucinations of at least moderate severity were characterized by significant macula and RNFL thinning relative to a control group.…”
Section: Potential Retinal Contributions To Vh and Visual Distortions In Schizophreniamentioning
confidence: 99%
“…Since the axons of the ganglion cells form the retinal nerve fibre layer (RNFL), ganglion cell loss may subsequently result in RNFL thinning 13 , 14 . Although RNFL thinning has been associated with the occurrence of VH 15 , this observation has been contradicted by others 16 . In a very recent study, that included all retinal layers, the combined GCL-IPL correlated best with reduced low contrast visual acuity and visual cognition outcomes in Lewy body disease 17 .…”
Section: Introductionmentioning
confidence: 90%